Incidence of second primary malignancies after autologous transplantation for multiple myeloma in the era of novel agents - Sahebi, Firoozeh; Schönland, Stefan (Biology of blood and marrow transplantation, 2018)
The advent of novel agents for multiple myeloma (MM) is cause for a re-examination of the incidence of second primary malignancies (SPMs). We examined the SPM rate in MM patients who were enrolled in the prospective observational CALM (Collaboration to Collect Autologous Transplant outcome in Lymphoma and Myeloma) study. Between 2008 and 2012, 3204 patients with MM underwent a first autologous hematopoietic stem cell transplantation. Plerixafor was used as a mobilizing agent for patients with poor (or potentially poor) stem cell mobilization as defined by the respective centers. A total of 135 patients developed SPMs, with a cumulative incidence of 5.3% (95% confidence interval, 4.4 to 6.3) at 72 months. Ninety-four patients developed solid tumors, 30 developed hematologic malignancies, and 11 developed an SPM of an unknown type. The cumulative incidence of known hematologic and solid malignancies were 1.4% and 3.6%, respectively, at 72 months. In a univariate analysis, use of radiotherapy, type of induction regimen, hematopoietic stem cell dose, poor mobilizer status, plerixafor use, and sex did not influence the cumulative incidence of SPMs. Only age over 65 years was statistically associated with an increased incidence. Overall, the incidence of SPMs was comparable to earlier estimations of SPMs in MM.